One-pot co-catalysis of corncob with dilute hydrochloric acid and tin-based solid acid for the enhancement of furfural production. (November 2018) - Jiang, Chun-Xia; Di, Jun-Hua; Su, Chun; Yang, Si-Yu; Ma, Cui-Luan; He, Yu-Cai
Graphical abstract: Highlights: Furfural was synthesized via co-catalysis of corncob with HCl plus SO4 2− /SnO2 -DTM. The relationship between pKa of acid and TOF of co-catalysis was explored. γ-GVL–water (6:4, v/v) biphasic system was built for furfural production. High furfural yield (68.9%) from corncob was achieved under the optimum condition. An effective catalyst recycling was demonstrated. Abstract: A newly synthesized solid acid catalyst SO4 2− /SnO2 -diatomite was prepared for synthesizing furfural from corncob in the presence of homogeneous Brönsted acid. The relationship between pKa of Brönsted acid and turnover frequency (TOF) of co-catalysis with Brönsted acid plus SO4 2− /SnO2 -diatomite was explored on the conversion of corncob to furfural. HCl (pKa = −7.0) (0.5 wt%) plus SO4 2− /SnO2 -diatomite (3.6 wt%) gave the highest furfural yield (40.1%) with TOF value at 2.98 h −1 in the aqueous media. In the γ-valerolactone–water (6:4, v:v) biphasic media containing 15 g/L ZnCl2, one-pot conversion of corncob with co-catalysts gave a furfural yield of 68.9% at 170 °C for 30 min. Additionally, an efficient SO4 2− /SnO2 -diatomite recycling was achieved with a productivity of 15.6 g furfural/(g solid acid·day) after 5 cycles of repeated use. Clearly, this one-pot co-catalysis process has high potential application for furfural production in future.